THE EFFECTIVENESS OF USING CANVA AS A LEARNING MEDIA FOR TEACHING LEARNING READING COMPREHENSION - Verawati, Nia; Hersulastuti; Haryono, Purwo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research investigates the use of “Canva” for teaching learning reading, specially it is written in the tittle of this research thesis, that is “The Effectiveness of Using Canva as a learning media for Teaching Learning Reading Comprehension”. The research is conducted based on the main problem; 1) How is the effectiveness of using canva as a learning media for teaching reading comprehension at SMKN 1 Puloampel Serang Banten. This Research is aimed; To verify the effectiveness of using canva as a learning media on students reading comprehension at SMKN 1 Puloampel Serang Banten. To answer the question, the writer use an experimental research method. The writer collected data from 70 students spread in two class, one class as an experimental group (Accounting Class – AK) and another one is as a control group (Office Management – MP), by applied experimental research method. The population is the first grade of SMKN 1 Puloampel, Serang – Banten. The data were collected through a validated multiple choice reading comprehension test administered as a post test. The data were analyzed using an independent sample t-test. The results revealed that the mean score of the experimental class was 78, while the control class obtained a mean score of 51. The statistical analysis show that the t-value was 10.775 with a degree of freedom (df) 68 and a significance value (sig-2 tailed) of 0,000 which was lower than 0,05. Therefore, the alternative hypothesis (Ha) was accepted and the null hypothesis (H0) was rejected. The findings demonstrate that the implementation of canva significantly improves students’ reading comprehension achievement. The use of visually enriched and interactive digital media facilitates better understanding of text and increase students’ motivation in reading activities. Thus canva is pedagogically recommended as an innovative and effective instructional media for teaching reading in vocational high school. Keywords : Canva, reading comprehension, digital learning media, quasi- experimental design, vocational high school